Vă rog ajutati-mă
2. Fie funcția f: ℝ → ℝ , f(x) = 5x - 7
a) Să se calculeze f(3) ; f(1); f(-2); f(4)
b) Să se calculeze E = f(5) ⋅ (8)
c) Să se calculeze E = f(7) + (6)
3. Fie funcția f: ℝ → ℝ , f(x) = -2x + 6
a) Să se calculeze f(3) ; f(1); f(-2); f(4)
b) Să se calculeze E = f(5) ⋅ (8)
c) Să se calculeze E = f(7) + (6)
Răspunsuri la întrebare
2.
funcția f: ℝ → ℝ , f(x) = 5x - 7
a) Să se calculeze f(3) ; f(1); f(-2); f(4) :
f(3) =5*3-7=15-7=8 => f(3)=8
f(1)=5*1-7=5-7 => f(1)=-2
f(-2)=5*(-2)-7=-10-7 => f(-2)=-17
f(4)=4*5-7=20-7 => f(4)=13
b) Să se calculeze E = f(5) ⋅ (8)
E=f(5) * (8) =?
f(5) = 5*5-7=25-7=18
E=f(5)*(8)=18*8=144
c) Să se calculeze E = f(7) + (6)
E=f(7)+(6) =?
f(7) = 7*5-7=35-7=28
E=f(7)+(6)=28+6=34
3.
funcția f: ℝ → ℝ , f(x) = -2x + 6
a) Să se calculeze f(3) ; f(1); f(-2); f(4)
f(3)= (-2)*(+3)+6 = -6+6 => f(3)=0
f(1)=(-2)*1+6=-2+6=4 => f(1)=4
f(-2)= (-2)*(-2)+6=4+6 => f(-2)=10
f(4)=(-2)*4+6= - 8+6 =>f(4)= -2
b) Să se calculeze E = f(5) ⋅ (8)
E=f(5) * (8) =?
f(5)=(-2)*5+6=-10+6= -4
E=f(5)*(8)= (-4) * 8 =
E=f(5)*(8)= -32
c) Să se calculeze E = f(7) + (6)
E=f(7) + (6)
f(7) =(-2)*7+6= -14 +6 = -8
E=f(7)+(6) = -8 + 6 = -2